2014
DOI: 10.1371/journal.pone.0111674
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Patient Survival in Cases of Acute Paraquat Poisoning

Abstract: Paraquat concentration-time data have been used to predict the clinical outcome following ingestion. However, these studies have included only small populations, although paraquat poisoning has a very high mortality rate. The purpose of this study was to develop a simple and reliable model to predict survival according to the time interval post-ingestion in patients with acute paraquat poisoning. Data were retrospectively collected for patients who were admitted with paraquat poisoning to Soonchunhyang Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
3
14
1
1
Order By: Relevance
“…Baseline laboratory parameters and initial patient information recorded at hospital arrival are summarized in Table 2. Overall mortality rate was 66.1%, similar to the mortalities rates in previous studies123. Semi-quantitative dithionite tests revealed that 27 patients had grade 1+ (blue color), 22 patients had grade 2+ (tender blue), and 60 patients had grade 3+ (dark blue) paraquat levels.…”
Section: Resultssupporting
confidence: 84%
“…Baseline laboratory parameters and initial patient information recorded at hospital arrival are summarized in Table 2. Overall mortality rate was 66.1%, similar to the mortalities rates in previous studies123. Semi-quantitative dithionite tests revealed that 27 patients had grade 1+ (blue color), 22 patients had grade 2+ (tender blue), and 60 patients had grade 3+ (dark blue) paraquat levels.…”
Section: Resultssupporting
confidence: 84%
“…Over the last decade (2006‐2015), marked progress has been made in the area of paraquat intoxication research. Clinical toxicology research on paraquat intoxication increased rapidly in this decade, and these clinical studies provide evidence of increased risk of mortality, the association between plasma paraquat level and outcome of paraquat poisoning, immunosuppressive therapy in lung fibrosis, and early haemoperfusion and the improvement of survival chances of severely paraquat‐poisoned patients …”
Section: Discussionmentioning
confidence: 99%
“…The most powerful model of the three was composed of serum paraquat level and the ingestion time. But the limitations of the study were its retrospective design and the uneasy reach of serum paraquat test in clinical practice 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the unstable power of the single factors and the complex of the traditional scores, and different from most of the above retrospective study, our report is prospective design and our model is based on the most routine test in clinical work 39 .…”
Section: Discussionmentioning
confidence: 99%